CASE STUDY APPROACH IN SECOND LANGUAGE LEARNING RESEARCH - Bambang Yudi Cahyono (Soegijapranata Catholic University, 2002)
The purpose of this anicle is to discuss methodological issues of the case study as an approach in second Im.guage learning research. It firstly analyses the positioll of case sludy in lhe conlinuum of research design. It then discusses the advalllages of using the case study approach to examine L2 learning. alld highlights some types of research questions thai can be addressed usillg this approach. Furthemwfe, the limi.tations of case study will be examined and the ways to deal with them will be discussed. Finally, this article analyzes samp'e case studies recently conducted to provide insights on how this approach can be applied usefully in the context of second language learning.